Development of Primary School Teacher Performance Assessment Instruments Based on Main Duties and Functions - Juria Sari; Zainuddin Zainuddin; Syamsul Arif Siregar (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to: create a teacher performance assessment instrument based on main tasks and functions; observe how the teacher performance assessment instrument developed can assess teacher performance well; find out the validity of the teacher performance assessment instrument developed according to material experts and design experts; and find out How effective was the teacher performance assessment instrument developed? The research was conducted at the Region II Elementary School (SD) Sei Rampah District, Serdang Bedagai Regency, in January–March 2024, using descriptive data analysis techniques. The development of the training model was carried out using the Thiagarajan Four-D (4-D) development model, which consists of four stages: define, design, develop, and disseminate. Data collection techniques used were interviews, questionnaires, and interviews, which were analyzed descriptively. Research subjects are expert validators, supervisors, school principals, and teachers. The research product is a teacher performance assessment instrument based on the main tasks and functions. The results of the material expert assessment show that in the very good category, the average percentage is 87.50% (very good), design experts are at 90.50% (very good), principal respondents are at 88.50% (very good), and teacher respondents are at 87.44% (very good). Furthermore, teacher performance assessment instruments based on main tasks and functions can be used in implementing teacher performance assessments